2007
DOI: 10.1210/en.2006-1475
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with Anticatabolic Agents Blunts But Does Not Eliminate the Skeletal Anabolic Response to Parathyroid Hormone in Oophorectomized Mice

Abstract: Previous studies have indicated that bisphosphonate pretreatment can inhibit the anabolic actions of PTH. We examined the capacity of two anticatabolic agents with different mechanisms of action, alendronate and osteoprotegerin (OPG), to influence the anabolic activity of PTH. Oophorectomized mice were pretreated for 30 d with alendronate or OPG and then treated for 30 d with the respective anticatabolic alone or the respective anticatabolic plus PTH(1-34). Bones were analyzed by bone mineral density (BMD), mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
31
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 25 publications
5
31
2
Order By: Relevance
“…Together, these data suggest inTo our knowledge, the skeleton of SCID/Beige mice has not been previously characterized regarding its response to exogenous intermittent PTH 1-34. However, the SCID/Beige mouse was developed on a C57BL/6J background [31]; arguably the most widely employed mouse strain in studies of PTH action on bone [12,13,17,19,32,33]. Our observations of increased serum osteocalcin, number of osteoblasts, and trabecular thickness are consistent with reports describing PTH 1-34 induced bone remodeling in C57BL/6J mice [12,32].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Together, these data suggest inTo our knowledge, the skeleton of SCID/Beige mice has not been previously characterized regarding its response to exogenous intermittent PTH 1-34. However, the SCID/Beige mouse was developed on a C57BL/6J background [31]; arguably the most widely employed mouse strain in studies of PTH action on bone [12,13,17,19,32,33]. Our observations of increased serum osteocalcin, number of osteoblasts, and trabecular thickness are consistent with reports describing PTH 1-34 induced bone remodeling in C57BL/6J mice [12,32].…”
Section: Discussionsupporting
confidence: 88%
“…This discrepancy may be attributed to the lower dose of PTH 1-34 and/ or the timing of end stage analysis of bone turnover markers employed in this study. Elevations in bone resorptive parameters (osteoclast number and activity) have been reported when PTH 1-34 is administered intermittently, at doses of 40 µg/kg and higher, over a time course similar to the present investigation [12,19,26]. Herein the highest dose of PTH 1-34 administered was 2-4 times less than those typically administered; a dose that may be insufficient to increase osteoclast number or activity.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Although it has been shown that bisphosphonates may clinically impair the anabolic actions of PTH, this is not always the case in rodent models. Studies have shown that co-treatment with PTH and alendronate increased its anabolic effect [37], whereas pre-treatment with bisphosphonates blunted but did not abolish the anabolic response to PTH on the skeleton of oophorectomized mice [38]. In the present study, the concurrent initiation of PTH therapy and therapy with ZA increased percent bone volume in comparison to ossicles treated with PTH or ZA alone.…”
Section: Discussioncontrasting
confidence: 45%
“…Consequently, PTH exerts greater effects on endosteal surfaces than on the periosteum, where remodeling is virtually absent, at least in adults. In turn, RANKL inhibitors may restrict PTH anabolic effects on endosteal surfaces, without affecting bone formation at the periosteum (7)(8)(9). PTH has also been shown to inhibit sclerostin (Sost) expression (10), and this effect is mediated by MEF2C (11,12).…”
mentioning
confidence: 99%